Productivity Calculation of Well Tlj-250 Post Hydraulic Fracturing Job at Pt . Bukit Apit Bumi Persada - Indarti, Adrian; Kusrini, Desi; Agriandita, Isnani; Prakoso, Rio Dwi (Universitas Wiralodra, 2024)
PT Bukitapit Bumi Persada is a company engaged in oil well service including cementing, stimulation, fracturing, coiled tubing unit and nitrogen service. Hydraulic fracturing is a stimulation activity to repair wells due to damage to the formation by injecting fracturing fluid at high pressure to create channels and held with proppant so that the fractures formed do not close again. The TLJ-250 well in the Prabumulih field was stimulated using hydraulic fracturing on Sunday, April 24, 2022. The TLJ-250 well has sandstone lithology with low permeability of about 4 mD with a porosity value of 12% so that this well is not productive to produce hydrocarbons. The fracturing fluid used is water base fluid, which is a water-based fracturing fluid and the proppant used is carbolite 20/40. The process of hydraulic fracturing begins with a breakdown test, step rate test, mini frac, and main frac with the stages of injecting proppant starting with pre-pad, slug, pad, and flush. The reason for hydraulic fracturing in the TLJ-250 well is that the ex bore well is less economical when producing. After hydraulic fracturing, TLJ-250 well experienced an increase in permeability value of about 904.15 mD with an average permeability around 22.32 mD followed by an increase in productivity index (PI) with the Prats method around 3.75 and the Cinco-Ley method is around 3.57 times. The production rate at TLJ-250 well is 158 BFPD with oil production of 21 BOPD